ABOUT OPTIONS, PHILIP MORRIS USA ACCOMMODATION - A REASONABLE APPROACH TO PUBLIC-PLACE SMOKING (Tufts Archival Research Center, 2007)
Statement from Philip Morris describing their position on public smoking. Claims that the public wants to be able to accommodate both smokers and non smokers. States committement to developing new ways to accommodate smokers without providing an annoyance to non smokers.